(untitled) (Islas, 2023)
Introduction: This article provides an assessment of the philosopher Humberto Piñera Llera, based on the influences of the historical context in the process of shaping and consolidating his thinking. Methods: The research is based on the dialectical materialist approach, employing hermeneutic and historical logical study methods for the interpretation and explanation of his works, personalities, and bibliographic sources. These methods lead us to understand Humberto Piñera Llera’s thinking based on the influence of the historical context. Results: It can be affirmed that Humberto Piñera Llera’s thinking was influenced by three essential aspects: the restructuring of philosophy in Cuba, the adoption of the existentialist current, and his role in philosophical institutions of which he was a member and presided over. Conclusions: It is concluded that in Humberto Piñera Llera, the demands and peculiarities of his time determined him as a philosopher, educator, and individual with the highest moral and human qualities, committed to individual freedom.